LİTERARY SCHOOLS IN ISTANBUL IN THE THOUGHT OF HALİT ZİYA - Gül, Mehmet (Fırat University, 2021)
Halit Ziya (Uşaklıgil) explained his thoughts on Tanzimat literature in his work named, “Kırk Yıl” in which he wrote his literary memoirs. One of main elements that draw attention in the work is the author’s observations and opinions about the literary circles he visited here, after he went from Izmir to Istanbul. The author gathered those who worked on the path of classical literature under the roof of Muallim Naci School and those who worked on the path to new litrature under the roof of Namık Kemal School. Muallim Naci evaluated and his environment from a negative point of view. He stated that the writers belonging to this school produced Works within the framework of Divan literature. He accused the Muallim Naci School of having a narrow World view, which was devoted to the past. H eapproached Ebuzziya Tevfik, Recaizade Mahmut Ekrem and Samipaşazade Sezai with a positive perspective and praised these authors for giving Works within the framework of new literature. He depicted Ebuzziya Tevfik as kind and gentleman. He highlighted Recaizade Mahmut Ekrem in terms of lifestyle, wordview and literary criticism. Halit Ziya drew attention to the fact that Sami Paşazade Sezai is a powerful pen in prose.

Halit Ziya (Uşaklıgil) edebi hatıralarını kaleme aldığı Kırk Yıl adlı hatıratında Tanzimat edebiyatına dair düşüncelerini açıklar. Eserde dikkati çeken temel unsurlardan biri, yazarın İzmir’den İstanbul’a gittikten sonra burada ziyaret ettiği edebi çevreler hakkındaki gözlem ve görüşleridir. Yazar, klasik edebiyat çerçevesinde yazanları Muallim Naci Mektebi, yeni edebiyat yolunda yazanları da Namık Kemal Mektebi çatısı altında toplar. Muallim Naci ve çevresine olumsuz bir bakış açısıyla bakar, bu mektebe mensup yazarların Divan edebiyatı anlayışıyla edebi eser kaleme aldığını ifade eder. Muallim Naci Mektebini eskiye bağlı, yeniliğe kapalı ve dar bir dünya görüşüne sahip olmakla suçlar. Ebuzziya Tevfik, Recaizade Mahmut Ekrem ve Sami Paşazade Sezai’ye olumlu bir bakış açısıyla yaklaşır ve söz konusu yazarları yeni edebiyat çerçevesinde eser verdiği için över. Ebuzziya Tevfik’i kibar ve beyefendi biri olarak tanıtan yazar, Recaizade Mahmut Ekrem’i yaşam tarzı, dünya görüşü ve edebi eleştiri bakımından ön plana çıkarır. Sami Paşazade Sezai’nin ise nesirde güçlü bir kalem olduğuna dikkati çeker.
HALİT ZİYA’NIN DÜŞÜNCESİNDE İSTANBUL’DAKİ EDEBİ MEKTEPLER